Tax systems in European Union countries - Joumard, Isabelle (OECD Publishing, 2003)
Despite recent cuts, the tax-to-GDP ratio in most EU countries remains much higher than in other economies. The tax mix is also different, with high tax wedges on labour and a stronger reliance on consumption and environmentally related taxes. While there is not much room for cutting taxes significantly without downsizing public spending, further re-balancing the tax burden away from labour could contribute to better employment performance. Greater reliance on property taxes, which are low by international standards, less use of reduced VAT rates and tax incentives targeted to specific saving vehicles should be considered. EU countries' experience in reforming their tax system may also provide useful insights for other regions where international integration is deepening. The free movement of goods, people and capital within the EU area, combined with the advent of the single currency, has also affected the design of national tax systems and has brought to the fore a number of international taxation issues